2017
DOI: 10.1186/s12879-017-2390-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between Fcγ receptor IIA, IIIA and IIIB genetic polymorphisms and susceptibility to severe malaria anemia in children in western Kenya

Abstract: BackgroundNaturally-acquired immunity to Plasmodium falciparum malaria develops after several episodes of infection. Fc gamma receptors (FcγRs) bind to immunoglobulin G (IgG) antibodies and mediate phagocytosis of opsonized microbes, thereby, linking humoral and cellular immunity. FcγR polymorphisms influence binding affinity to IgGs and consequently, can influence clinical malaria outcomes. Specifically, variations in FcγRIIA -131Arg/His, FcγRIIIA-176F/V and FcγRIIIB-NA1/NA2 modulate immune responses through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 54 publications
5
25
1
Order By: Relevance
“…These amino acid changes are responsible for antigenic determinants named human immunoglobulin Gm (gamma markers) allotypes. There are four allotypes for IgG1 in the CH1 and CH3 constant domains called G1m [1,2,3,17], one allotype for IgG2 in the CH2 constant domain called G2m23 and thirteen allotypes for IgG3 in the CH2 and CH3 constant domains called G3m [5,6,10,11,13,14,15,16,21,24,26,27,28] (12,13). The most polymorphic G3m allotypes are distinguished by variations on nine amino acids (13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These amino acid changes are responsible for antigenic determinants named human immunoglobulin Gm (gamma markers) allotypes. There are four allotypes for IgG1 in the CH1 and CH3 constant domains called G1m [1,2,3,17], one allotype for IgG2 in the CH2 constant domain called G2m23 and thirteen allotypes for IgG3 in the CH2 and CH3 constant domains called G3m [5,6,10,11,13,14,15,16,21,24,26,27,28] (12,13). The most polymorphic G3m allotypes are distinguished by variations on nine amino acids (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the FcgRIIA 131RH heterozygous polymorphism was associated with malaria protection in some studies (31,32) while for Maiga et al (33), a marginal protective effect on parasitemia was observed in a Fulani group from Mali harboring the 131RR genotype. Munde et al (11) demonstrated that the FcgRIIA 131R-FcgRIIIA 176F-FcgRIIIB NA2 haplotype was important in conditioning susceptibility to malaria anemia (or increased levels of circulating parasites) in West Kenya. Ouma et al (34) reinforced the results obtained from independent analysis of FcgR (31,32) by showing a negative association between the FcgRIIA 131H-FcgRIIIB NA1 haplotype and severe malaria anemia and a positive one when considering the FcgRIIA 131H-FcgRIIIB NA2 haplotype.…”
Section: Introductionmentioning
confidence: 99%
“…SMA typically occurs in areas that have high exposure rates to Plasmodium or are genetically susceptible to the disease. FcγRIIIa is the lone Fc receptor expressed on NK cells that enables ADCC, and polymorphisms in FcγRIIIa are associated with SMA [97]. The cell responsible for this association is unknown, but lack of function mutations correlate with poorer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the frequencies of the H131 and R131 alleles vary according to ethnic grouping in Africa. Three different studies showed similar distributions of H131 homozygotes (27.37% out of 274 subjects, 32% out of 97 subjects, and 20.45% out of 88 subjects) in Luo and Luhya populations of Kenya and a Yoruba population of Nigeria (56,60). However, different distributions of the genotype for this SNP were found for different ethnic groups from Ghana (p=0.036), with the frequency of subjects who were homozygous for R131 being higher for the Ga-Adangbe ethnic group than for the Akan, Hausa and Fulani ethnic groups (p=0.01347; Chi square test performed by us and R according to the results given by the authors in the Supplementary Table in SI) (93).…”
Section: Genes Encoding Low-affinity Receptorsmentioning
confidence: 78%